Prevalence of subclinical ketosis in small backyard Holstein dairy farms in western cities of Turkey - Aksoy, K; Deniz, A; Pekmezci, A; Metin, M; Polat Dinçer, PF (Journal of the Hellenic Veterinary Medical Society, 2024)
ABSTRACT: The prevalence of subclinical ketosis (SCK) was investigated in small, family-run backyard dairy farms with 5-20 Holsteins in the villages of western cities in Turkey. A total of 168 multiparous and 60 primiparous cows in 130 farms were examined with a cow-side beta-hydroxybutyric acid (BHBA) analyser. The BHBA cut-off point for SCK diagnosis was set at ≥ 1.2 mmol/L. Cows in the study were grouped according to days 0-7 (PP0-7), 8-15 (PP8-15), 16-28 (PP16-28), 0-15 (PP0-15), and 0-28 (PP0-28) postpartum. Overall SCK prevalence in PP0-28 was 26.8%. It was 16.4, 26.4 and 35.8% in PP0-7, PP8-15, and PP16-28 (p<0.05), respectively. It was 23.7 and 35.6% in multiparous and primiparous, respectively. For multiparous it was 19.4 and 35.6% and for primiparous 35.1 and 36.4 % in PP0-15 and PP16-28, respectively. The odds ratio was 2.26 and 1.04 for primiparous compared to multiparous in PP0-15 and PP16-28, respectively. Odds were 1.55 and 2.85 for PP16-28 compared to PP8-15 and PP0-7, respectively. It was 1.83 for PP8-15 compared with PP0-7. The prevalence was much higher in primiparous cows than in multiparous cows in seasons other than summer (p<0.05). In conclusion, the prevalence of SCK was much higher than in the large integrated farms previously reported in Turkey. The risk of SCK is higher in PP8-15 and PP16-28 than in PP0-7. Primiparous cows were more frequently affected by SCK than multiparous cows, especially in the first two weeks after calving and in the other seasons except for summer. Key words: Subclinical ketosis; Holstein; backyard farm